Análisis del manejo agrotécnico con orientación agroecológica en la finca “María”, barrio Rumizhitana, cantón Loja, provincia de Loja - Solórzano Peña, Mabel Alejandra (2024)
This research aims to analyze the agrotechnical management, with an agroecological orientation in the farm "María" Rumizhitana Neighborhood, Loja Canton, Loja Province, in order to determine the agrotechnical practices used in the farm for the cultivation of its main agricultural products. For this, a methodology with a qualitative approach was used, with an exploratory-descriptive type of research, the research design was non-experimental, which through the application of research instruments such as the interview, observation sheet and SWOT analysis, it was possible to obtain results regarding the agrotechnical management of the "María" farm; As a main result, it was determined that it maintains a good management of crops, soil, irrigation, however, in terms of post-harvest treatment, they lack agroecological techniques. It is concluded that the "María" farm is carrying out a management plan according to the availability of the area and its financing; demonstrating that the integration of innovative sustainable techniques not only benefits the farm, but also contributes to the food sovereignty of the area, which is highly beneficial because it contributes to local production and consumption. Therefore, an agrotechnical management plan with an agroecological approach is proposed for the "María" farm, which includes specific strategies to improve agricultural sustainability and productivity, this is because agronomic management are techniques and practices applied throughout the agricultural system with the aim of improving the production and quality of agricultural products, and its importance lies in greater adaptability to changing conditions and significantly reducing dependence on external and chemical inputs that are highly harmful to nature and humans.